Pharmacological Interventions for REM Sleep Behavior Disorder in Parkinson's Disease: A Systematic Review - Yan, Junqiang; Liu, Anran; Huang, Jiarui; Wu, Jiannan; Shen, Ruile; Ma, Hongxia; Yang, Jianxue (Frontiers in Aging Neuroscience, 2021)
To review the therapeutic effects of drugs on REM sleep behaviour disorder (RBD) in Parkinson's disease (PD) by searching the MEDLINE/PubMed, Embase, Cochrane and CBM databases. According to the inclusion and exclusion criteria, studies were included after excluding duplicate data. We studied the improvement of RBD in patients with Parkinson's disease (PD-RBD) to evaluate by polysomnography the safety and efficacy of pharmacological intervention. This systematic review mainly describes the drugs that can be used to treat PD-RBD patients. THe studies have shown that melatonin can be used as the first-line drug for PD-RBD, and clonazepam provides significant improvement on PD-RBD. Studies have shown that rotigotine can be used as an alternative drug. However, further large-scale clinical trial studies are still needed to provide the best guidelines for the pharmacological treatment of PD-RBD.